Parental psychopathology and expressed emotion in children with avoidant/restrictive food intake disorder - Hannah Lea Klüber; Annick Martin; Franziska Schlensog-Schuster; Andreas Hiemisch; Wieland Kiess; Anja Hilbert; Ricarda Schmidt (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Family factors like parental psychopathology and parental expressed emotion, referring to the emotional atmosphere within a family, play a significant role in the maintenance and treatment outcome of anorexia nervosa. However, nothing is known about these parental characteristics in avoidant/restrictive food intake disorder (ARFID). Objective This study aimed to determine the proportion of parents exceeding clinical cutoffs for depression, eating disorder psychopathology, and expressed emotion, specifically criticism and emotional overinvolvement, in ARFID, anorexia nervosa (AN), and healthy controls (HC), and to evaluate group differences. Associations between parental characteristics and child illness characteristics were analyzed. Method Treatment-seeking children and adolescents (0–17 years) with ARFID (n = 42) were compared to those with AN (n = 25) and HC (n = 42) in parental eating disorder psychopathology (Eating Disorder Examination-Questionnaire 8), parental depression (Patient Health Questionnaire-9), and parental expressed emotion (Family Questionnaire). Results When comparing ARFID with AN and HC, the proportions of parents exceeding clinical cutoffs for depression (26% vs. 20% vs. 14%), eating disorder psychopathology (7% vs. 12% vs. 9%), and criticism (26% vs. 32% vs. 29%) did not differ significantly. For emotional overinvolvement (41% vs. 52% vs. 0%), differences emerged between ARFID and HC, but not AN. Dimensionally, levels of parental depressive symptoms and emotional overinvolvement were higher in those with ARFID versus HC only. More parental depressive symptoms, criticism, and emotional overinvolvement were significantly related to greater children’s restrictive eating behaviors, lower standardized body-mass-index, and lower number of accepted foods. Conclusion ARFID and anorexia nervosa were found to share similar distributions in parental psychopathology and parental expressed emotion. Future studies may focus on the role of those family factors in development and outcome of ARFID.